Beban Kerja Perawat Dengan Penerapan Patient Safety di Instalasi Gawat Darurat (IGD) - Anita Sompie; Faradilla Miftah Suranata; Suwandi I. Luneto (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Patient safety is an important aspect of care standards that must be considered by all healthcare providers. Risk assessment, identification and management of hazards, documentation, analysis, and follow-up of accidents, and recovery provisions to reduce risks and prevent injuries are part of patient safety. The objective of this study is to determine the relationship between nurse workload and the implementation of patient safety in the Emergency Department (IGD) of Maria Walanda Maramis Regional General Hospital. The research uses a cross-sectional design. The sample in this study consisted of 22 respondents using the purposive sampling technique. Data collection on workload and the implementation of patient safety was conducted using a questionnaire, and analyzed using the Spearman rho statistical test. The research results majority of the workload was found to be in the light category, with 15 respondents (68.2%). The application of patient safety in the least category was poor, with 6 respondents (27.3%), while the most was in the good category, with 16 respondents (72.7%). The results of the Spearman rho test obtained a p-value of 0.032 where < α 0.05. Conclusion: There is a relationship between the nurses' workload and the implementation of patient safety in the Emergency Room (IGD) of Maria Walanda Maramis Regional General Hospital. It is recommended that nurses become more aware of the importance of fatigue management and effective coping strategies to maintain the quality of patient care.